INFORMATION ABOUT HEALTHCARE-ASSOCIATED INFECTION REPORTED FROM A HOSPITAL-WIDE INCIDENCE STUDY: CONSIDERATIONS AND AWARENESS FOR INFECTION PREVENTION AND CONTROL PLANNING - Abdullah Ahmad Mohammed Al Abbas, Egbal Lateef Mefleh Al-Fadhli, Mased Ayedh Almutairi, Abeer Abbad AAlabbad, Ahmad nasser alrashidi , Hamad Saeed Hamad AL Yami, Abdullah saud saleh alhareth, Hamad Yahya Mahdi Al Rubaie, Nasser Mohammed Hussain Alajmi (Chelonian Research Foundation, 2022)
Introduction: Hospital-acquired infections (HAIs) pose significant challenges, leading to increased hospital stays, elevated healthcare costs, and higher mortality rates, particularly in vulnerable patient populations. The identification ofpatients at greatest riskfor HAIs is crucial for focusing on prevention, management; and monitoring efforts. This comprehensive review encompasses a wide range of strategies aimed at mitigating the risk of nosocomial infections. Methods: This systematic review assessed the impact of hospital design modifications on the incidence of HAIs across various departments, including Intensive Care Units (ICUs), surgical units, isolation wards, and general hospital settings. We included both experimental and observational studies published in English up to the year 2021. A detailed search strategy employed keywords relating to hospital design and HAIs across multiple medical databases, suppleml ented by manual searches of bibliographies, consultations with experts in hospital hygiene, and exploration ofdigital resources. The primary endpoint analyzed was the infection rate within these healthcare environments. Results: From the 178 papers that met our initial screening criteria, 17 studies comprising concurrent or historical cohort analyses—were relevant for in-depth evaluation. These studies predominantly fell into the lower tier of the evidence hierarchy, lacking in higher-level evidence such as meta-analyses or randomized controlled trials. Architectural interventions typically included expanding the space allocated per bed, transitioning to single-patient rooms, and enhancing the accessibility of hand hygiene facilities. Among these interventions, three studies demonstrated a significant reduction in HAI rates post- implementation. Nonetheless, there was a notable absence of research focusing on a broader spectrum of HAIs, including postoperative pneumonia and urinary infections. Conclusions: Comprehensive infection control measures, including the judicious use of antimicrobials and prophylactic strategies, are paramount in the fight against HAIs. The adoption of robust surveillance systems, which integrate datafrom a variety ofsources and undergo regular scrutiny for performance, is critical for the successful deployment of prevention and control initiatives. These efforts, combined with ongoing enhancements to hospital infrastructure, can play a pivotal role in minimizing the burden of HAIs, thereby safeguarding patient health and optimizing healthcare delivery. Keywords: Hospitals, Infections, Bacteria, Health workers, Surveillance.